DETERMINANTS OF KNOWLEDGE ABOUT NEONATAL DANGER SIGNS AMONG FIRST-TIME MOTHERS IN PAKISTAN: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Introduction: The neonatal period, the first 28 days of life, is a critical window of vulnerability. Pakistan’s neonatal mortality rate was approximately 37.6 per 1,000 live births in 2024, among the highest in South Asia . Most neonatal deaths occur at home, often because of delayed recognition of neonatal danger signs (NDSs). First-time mothers are particularly at risk due to limited experience. Identifying socio-demographic and obstetric determinants of maternal knowledge is essential for early recognition and timely care-seeking.Objective: To examine socio-demographic and obstetric factors influencing knowledge of neonatal danger signs among first-time mothers in Pakistan.Methods: A hospital-based cross-sectional study was conducted from September 1, 2022, to February 28, 2023, in the maternity wards of Liaquat University Hospitals, Jamshoro and Hyderabad, Sindh. Using purposive sampling, 300 primiparous women were recruited. A structured, prevalidated questionnaire assessed knowledge of 12 WHOrecommended danger signs (e.g., poor feeding, convulsions, lethargy, thermal extremes). Knowledge scores were categorized as low (0–4), average (5–8), or high (9–12). Associations with socio-demographic and obstetric variables were analyzed using chi-square and multivariate logistic regression (SPSS26; p ≤ 0.05).Results: Among participants, 84% were aged 18–28 years, 65.3% had no formal education, and 86.7% were unemployed. Knowledge levels were: low 35.7%, average 53.7%, high 10.7%. Fever was recognized by all, followed by poor feeding and rapid breathing. Significant predictors of higher knowledge included maternal education (AOR 2.15; 95% CI 1.28–3.61), ≥4 antenatal visits (AOR 1.89; 95% CI 1.12–3.19), and receiving neonatal care education (AOR 3.02; 95% CI 1.74–5.24).Conclusion: Maternal knowledge of neonatal danger signs at hospital discharge in Pakistan is low. Strengthening antenatal and postnatal education—especially targeting less-educated and socioeconomically disadvantaged mothers—with culturally tailored counseling is essential to promote early recognition of neonatal illnesses and improve outcomes.